Histogram-based analysis for confocal microscope images with immunofluorescent staining: A graphical-user-interface tool - Xiuli Yang; Yuguo Li; Zhiliang Wei (MethodsX)
Immunofluorescent staining is widely utilized in biomedical research. However, reliable and reproducible quantification remains challenging and often depend on the experience of the raters heavily. As a result, variations caused by different raters or the same rater at different times confound quantitative interpretations. In this study, we propose a histogram-based analytical method to explore the sources of signals at various intensities and, subsequently, identify the signals of interest using the histograms as a reference. Our method aims to alleviate inter-rater and intra-rater inconsistencies and improve the quantification of microscope images with immunofluorescent staining. • Identification of signal sources for image pixels at different intensities • Reduction of quantification variations using the proposed histogram-based analysis